PENGARUH EXPERIENTIAL MARKETING TERHADAP WORD OF MOUTH, DI MEDIASI CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY (Studi Kasus: PT. Kereta Api Indonesia) - Aulia Izzatur Rohima (CBJIS: Cross-Border Journal of Islamic Studies, 2022)
This study aims to determine the effect of experiential marketing, word of mouth mediated by customer satisfaction and customer loyalty with a case study of PT. Kereta Api Indonesia. This research uses structural equation model (SEM) analysis. The data used in this study is secondary data collected using a questionnaire from consumers who have used PT. Indonesian Railways at least 1 time Before the pandemic and at least 1 time during the pandemic, the respondents collected in this study were 251 respondents. The method used is the Stuctural Equation Model with AMOS 24 software. The results of this study indicate that experiential marketing has a positive and significant effect on customer satisfaction, customer loyalty and word of mouth, while customer satisfaction has a positive and significant effect on customer loyalty and word of mouth, however. customer loyalty has a positive but not significant effect on word of mouth. Meanwhile, the relationship between experiential marketing and word of mouth mediated by customer satisfaction and customer loyalty got significant results and the relationship between customer satisfaction and word of mouth mediated by customer loyalty got significant results.